DEKOMPOSISI SAMPAH JANUR KELAPA (Cocos nucifera L.) DAN NIBUNG (Oncosperma tigillarium (Jack) Ridl.) DALAM LUBANG RESAPAN BIOPORI - Candra Noviarta, I Putu; Raka Dalem, A.A. Gde; Watiniasih, Ni Luh (SIMBIOSIS; Vol 4 No 2 (2016))
ABSTRACT The increasing volume of garbage of Balinese Hindu’s offering is still a problem. The garbage, when it is decomposed however could be useful for fertilized. This organic litter can be decomposed in biopore. This research ainied to investigated the decomposition rate of C. nucifera and O. tigillarium litter in biopores. This research was conducted between February and July 2015. Garbage were collected from temples in Jembrana city and treated at Dangin Tukadaya village, Jembrana Distric. Sampels were arranged in a Factorial Randomized Blocked Sampling Design 2 factors i.e: treatments and times (1, 2, 3, 4 and 23 weeks). The result showed that decomposition rate 98,63% of cocos litter and 99,23% of oncosperma litter were decomposed in biopore on week 23 compared to 89,06% of cocos and 75,76 % of oncosperma litter in control. Decomposition mean rate is 9,33 %/week of cocos litter and 9,64 %/week of oncosperma litter were decomposed in biopore but in control is 7,85 %/week of cocos and 8,07 %/week of oncosperma litter. Total cocos and oncosperma litter decomposition took about 23,3 and 23,2 weeks in biopore but for control 25,8 and 30,4 weeks The number of millipedes ( Harpaphe haydeniana ) as decomposer was found higher compared to other decomposers such as earth worms and molusca. Keywords: decomposition, biopore, decomposer, bali, cocos litter, oncosperma litter
Keywords: decomposition, biopore, decomposer, bali, cocos litter, oncosperma litter